This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The above exponential equation can be rewritten as ( 3 3 ) x 1 + ( 2 2 3 1 ) x 1 = 2 ( 2 3 ) x 1 , or ( 3 x 1 ) 3 + ( 3 x 1 ) ( 2 x 1 ) 2 = 2 ( 2 x 1 ) 3 . Now, let u = 3 x 1 , v = 2 x 1 so that we obtain the quadratic:
u 3 + u v 2 = 2 v 3 ;
or u 3 − v 3 = v 3 − u v 2 ;
or ( u − v ) ( u 2 + u v + v 2 ) = − v 2 ( u − v ) ;
or u 2 + u v + 2 v 2 = 0 ;
or u = 2 − v ± v 2 − 4 ( 1 ) ( 2 v 2 ) = 2 − v ± − 7 v 2 = ( 2 − 1 ± 7 i ) ⋅ v ;
or v u = ( 2 3 ) x 1 = 2 − 1 ± 7 i .
Hence, we have the ratio of two real numbers equaling one of two non-zero complex numbers ⇒ C O N T R A D I C T I O N . There is no x ∈ R that solves the above original exponential equation.